Workplace interventions for smoking cessation. - Moher, M; Hey, K; Lancaster, T (2005)
BACKGROUND: The workplace has potential as a setting through which large groups of people can be reached to encourage smoking cessation. OBJECTIVES: To categorize workplace interventions for smoking cessation tested in controlled studies and to determine the extent to which they help workers to stop smoking or to reduce tobacco consumption. SEARCH STRATEGY: We searched the Cochrane Tobacco Addiction Group Specialized Register in October 2004, MEDLINE (1966 - October 2004), EMBASE (1985 - October 2004) and PsycINFO (to October 2004). We searched abstracts from international conferences on tobacco and we checked the bibliographies of identified studies and reviews for additional references. SELECTION CRITERIA: We categorized interventions into two groups: a) Interventions aimed at the individual to promote smoking cessation and b) interventions aimed at the workplace as a whole. We applied different inclusion criteria for the different types of study. For interventions aimed at helping individuals to stop smoking, we included only randomized controlled trials allocating individuals, workplaces or companies to intervention or control conditions. For studies of smoking restrictions and bans in the workplace, we also included controlled trials with baseline and post-intervention outcomes and interrupted times series studies. DATA COLLECTION AND ANALYSIS: Information relating to the characteristics and content of all kinds of interventions, participants, outcomes and methods of the study was abstracted by one author and checked by two others. Because of heterogeneity in the design and content of the included studies, we did not attempt formal meta-analysis, and evaluated the studies using qualitative narrative synthesis. MAIN RESULTS: Workplace interventions aimed at helping individuals to stop smoking included ten studies of group therapy, seven studies of individual counselling, nine studies of self-help materials and five studies of nicotine replacement therapy. The results were consistent with those found in other settings. Group programmes, individual counselling and nicotine replacement therapy increased cessation rates in comparison to no treatment or minimal intervention controls. Self-help materials were less effective.Workplace interventions aimed at the workforce as a whole included 14 studies of tobacco bans, two studies of social support, four studies of environmental support, five studies of incentives, and eight studies of comprehensive (multi-component) programmes. Tobacco bans decreased cigarette consumption during the working day but their effect on total consumption was less certain. We failed to detect an increase in quit rates from adding social and environmental support to these programmes. There was a lack of evidence that comprehensive programmes reduced the prevalence of smoking. Competitions and incentives increased attempts to stop smoking, though there was less evidence that they increased the rate of actual quitting. AUTHORS' CONCLUSIONS: We found: 1. Strong evidence that interventions directed towards individual smokers increase the likelihood of quitting smoking. These include advice from a health professional, individual and group counselling and pharmacological treatment to overcome nicotine addiction. Self-help interventions are less effective. All these interventions are effective whether offered in the workplace or elsewhere. Although people taking up these interventions are more likely to stop, the absolute numbers who quit are low. 2. Limited evidence that participation in programmes can be increased by competitions and incentives organized by the employer. 3. Consistent evidence that workplace tobacco policies and bans can decrease cigarette consumption during the working day by smokers and exposure of non-smoking employees to environmental tobacco smoke at work, but conflicting evidence about whether they decrease prevalence of smoking or overall consumption of tobacco by smokers. 4. A lack of evidence that comprehensive approaches reduce the prevalence of smoking, despite the strong theoretical rationale for their use. 5. A lack of evidence about the cost-effectiveness of workplace programmes.